2005
DOI: 10.1002/pat.580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma irradiation on HDPE/HA (80:20) composites

Abstract: Effect of gamma irradiation on high density polyethylene/hydroxyapatite (HDPE/HA) composites prepared by solution was studied. Melt flow index (MFI) showed a strong increase with radiation due to some decalin remnant. The evaluation of the mechanical behavior showed an increase in the Young's modulus and resistance at break values attributed to the HA addition. Elongation at break decrease strongly. Radiation did not produce any significant changes on crystallization temperatures. Crystallinity of the polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…On the other hand when HA is added to the polymer, the material viscosity increases and hence resistance to flow increases. Similar results have been also obtained where the MFI decreases due to irradiation and presence of HA for HDPE/HA (20:80) [ 29 ].
Figure 2 Effects of HA and Gamma radiation on the HDPE melt flow index (MFI).
…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand when HA is added to the polymer, the material viscosity increases and hence resistance to flow increases. Similar results have been also obtained where the MFI decreases due to irradiation and presence of HA for HDPE/HA (20:80) [ 29 ].
Figure 2 Effects of HA and Gamma radiation on the HDPE melt flow index (MFI).
…”
Section: Resultssupporting
confidence: 84%
“…This weight loss mainly occurred in the range of 433-495°C with negligible change at temperature higher than 505°C. Also, the improvements in the nanocomposite thermal stability due to irradiation can be attributed to the reduction of chain mobility which occurred as a positive effect due to gamma irradiation [ 29 ].
Figure 6 Thermogravimetric analyses of HDPE and its nanocomposite (a) Effect of HA ratio (b) Effect of Irradiation Dose.
…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the modulus of elasticity in tension and tensile strength increased with increasing the radiation dose while the fracture strain decreased. Albano et al [ 22 ] studied the effect of gamma irradiation on properties of HDPE/HA composites prepared by solution. Results indicated strong increase in MFI with radiation dose while remarkable decrease in the crystallinity and melting temperature of HDPE/HA composites.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, no measurable influence of the 25 kGy irradiation dose was observed on the properties of HDPE−HA composites. 65 Considering the lower viscosity of HDPE compared to that of UHMWPE, the addition of an appropriate amount of HDPE to UHMWPE is expected to enhance the processibilty, by reducing the melt viscosity. 51 Furthermore, we have recently demonstrated that the dispersion of GO and interfacial adhesion between GO and HDPE can be improved by immobilizing PE onto GO sheets.…”
Section: Resultsmentioning
confidence: 99%